Penerapan Model Pembelajaran Awareness training Berbantuan e-LKPD untuk Meningkatkan Minat Belajar Peserta Didik - Olivia, Maria Afrini; Wea, Kristiana Nathalia; Riong, Maria Bernadeta Dua (PendIPA Journal of Science Education, 2024)
This study was conducted based on the results of observations obtained, namely the lack of interest in learning physics among students at school and students more often using mobile phones during the physics learning process in class. The study aims to see the interest of students in participating in physics learning using the awareness training learning model assisted by e-LKPD media. This study is a qualitative descriptive study with the instrument used in the form of a student learning interest questionnaire. Before the questionnaire was used, validation was carried out first. The instrument was declared valid and suitable for use with an Aiken V index value of 0.81. The results of this study showed that physics learning using the awareness training learning model assisted by e-LKPD media can make students interested in participating in physics learning. This can be seen from the results of the questionnaire obtained by 89.69% which is in the very interested category.